2022
DOI: 10.1186/s12885-022-10026-3
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to oral anticancer agent treatment in older adults with cancer: a secondary analysis of data from electronic health records and a pilot study of patient-reported outcomes

Abstract: Background More than 60% of cancer cases occur in older adults, and many are treated with oral anticancer agents. Yet, the treatment tolerability in older adults has not been fully understood due to their underrepresentation in oncology clinical trials, creating challenges for treatment decision-making and symptom management. The objective of this study was to investigate the tolerance of capecitabine, an example of oral chemotherapy, among older adults with cancer and explore factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
(52 reference statements)
3
4
0
Order By: Relevance
“…In addition, consistent with other studies [ 22 , 23 ], our study showed a significant association between HFS and increasing age. Older patients often present with pre-existing comorbidities and are prescribed with multiple concurrent medications [ 22 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, consistent with other studies [ 22 , 23 ], our study showed a significant association between HFS and increasing age. Older patients often present with pre-existing comorbidities and are prescribed with multiple concurrent medications [ 22 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, consistent with other studies [ 22 , 23 ], our study showed a significant association between HFS and increasing age. Older patients often present with pre-existing comorbidities and are prescribed with multiple concurrent medications [ 22 , 24 ]. Furthermore, a study showed that elderly patients may have reduced drug clearance, leading to higher capecitabine exposure compared to younger individuals [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, consistent with other studies [24,25], our study showed a signi cant association between HFS and increasing age. Older patients, often more frail with potential pre-existing comorbidities and concurrent use of multiple medications, are at an increased risk of adverse reactions to cancer treatment [24,26].…”
Section: Discussionsupporting
confidence: 93%
“…We also found that female patients were more prone to develop more severe HFS. Sex and gender difference in capecitabine toxicity has been previously reported [24,27], possibly attributed to varying body compositions between males and females [28,29]. A study showed that female colorectal cancer patients had more dose-limiting toxicity than male patients when given capecitabine based on their body surface area [27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, treatment protocols for older patients often focus more on oral therapies and avoid intensive therapies such as chemotherapy due to the convenience and exibility in the administration process. [17] Our study did not include oral therapies administered at home, as their contribution to time toxicity is limited. [13,18,19] Less intensive treatment is commonly received by very old patients, because of factors such as prevalence of comorbidities, lower life expectancy, and increased risk of adverse effects contributing to the perception that multi-modal treatments may be less favorable for this patient population, as well as patient preference and shared decision making .…”
Section: Discussionmentioning
confidence: 99%